PENGARUH KETERAMPILAN MENGAJAR GURU DALAM PEMBELAJARAN JARAK JAUH DAN MOTIVASI BELAJAR ONLINE TERHADAP HASIL BELAJAR EKONOMI SISWA SMAN 1 SOLOK - Gumanti, Dessyta (Universitas Negeri Yogyakarta, 2023)
This research was carried out with the first objective of knowing the effect of the teacher's teaching skills in distance learning on the online learning motivation of students in economics at SMAN 1 Solok. The second objective is to determine the effect of the teacher's teaching skills in distance learning on learning outcomes and the last objective is to determine the effect of the teacher's skills in distance learning on learning outcomes that are intervened by the online learning motivation variable. The study was conducted at SMAN 1 Solok with a total population of 432, then a sample was drawn using the proportional random sampling technique to obtain a sample of 123 students. This study uses a causal survey method. The research data was collected using a research instrument in the form of a questionnaire with a Likert scale and also the student's UAS scores for the processed learning outcome variables were analyzed using path analysis techniques. Data dissemination is done using Google Forms. The results of hypothesis testing obtained 1) Teacher teaching skills in distance learning have a significant effect on students' online learning motivation for economic subjects at SMAN 1 Solok (H1 is accepted), 2) Teacher teaching skills in distance learning have a significant effect on student learning outcomes in SMAN economic subjects. 1 Solok (H2 is accepted), 3) Teacher's teaching skills in distance learning have a significant effect on student learning outcomes mediated by online learning motivation for economic subjects at SMAN 1 Solok (H3 is accepted).